An Analysis of Pentagon Fraud in Sustainability Reporting and the Role of Behavioral Organizations as an Intervention Solution - Sutrisno (RADJA PUBLIKA, 2025)
Sustainability reporting is increasingly adopted as a strategic tool for organizations to communicate their environmental, social, and governance (ESG) practices. However, the potential for fraud—driven by the desire to uphold a green image and weak regulatory frameworks—has led to the manipulation of such disclosures. This study critically explores the Pentagon Fraud theory, which expands upon previous fraud frameworks by including arrogance and competence alongside pressure, opportunity, and rationalization. The primary objective of this research is to investigate how each of these five elements influences the tendency for fraud in sustainability reports. Moreover, it examines the role of organizational behavior as an intervention strategy to mitigate fraud risk. Using a qualitative literature review method, the study synthesizes data from scholarly articles, institutional reports, and empirical studies published between 2019 and 2024. Through thematic content analysis, it uncovers how fraud in sustainability reporting is frequently triggered by opportunity and rationalization, enabled by limited oversight and reputational pressure. Furthermore, the study identifies organizational behavior—especially ethical leadership, internal control systems, and whistleblowing mechanisms—as a critical deterrent to fraudulent activities. The findings suggest that integrating behavioral ethics into organizational governance and ESG reporting systems is vital for fraud prevention. The study contributes a conceptual model combining the Pentagon Fraud framework with behavioral interventions, offering both theoretical insight and practical guidelines for organizations, regulators, and auditors to enhance reporting credibility and integrity.